2021
DOI: 10.1007/s42399-020-00690-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence on Multisystem Inflammatory Syndrome in Children Associated with SARS-CoV-2 Infection: a Systematic Review with Meta-analysis

Abstract: With the increased spread of severe acute respiratory syndrome coronavirus 2 infection, more patients with multisystem inflammatory syndrome in children (MIS-C) are being reported worldwide. This systematic review with meta-analysis aims to analyse the clinical features, proposed pathogenesis and current treatment options for effective management of children with this novel entity. Electronic databases (Medline, Google Scholar, WHO, CDC, UK National Health Service, LitCovid, and other databases with unpublishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(124 citation statements)
references
References 28 publications
8
84
0
14
Order By: Relevance
“…e use of cytokine inhibitors tocilizumab, anakinra, and baricitinib is a potential option for the treatment of severe COVID-19 [33], but none of them have been investigated in prospective clinical trials in the pediatric population. In five reviews among patients with MIS-C, the following therapies were employed: intravenous immunoglobulin (63-100%), corticosteroids (49-70%), anakinra (8-13%), tocilizumab (6.5-27%), remdesivir (3-8%), infliximab (1.2-8%), and plasma (n � 3) [24,26,27,29,[36][37][38]. Intravenous immunoglobulin combined with methylprednisolone compared to intravenous immunoglobulin alone is significantly effective in reducing fever, the need for second-line drug therapy, hemodynamic support, and length of intensive care stay [39].…”
Section: Discussionmentioning
confidence: 99%
“…e use of cytokine inhibitors tocilizumab, anakinra, and baricitinib is a potential option for the treatment of severe COVID-19 [33], but none of them have been investigated in prospective clinical trials in the pediatric population. In five reviews among patients with MIS-C, the following therapies were employed: intravenous immunoglobulin (63-100%), corticosteroids (49-70%), anakinra (8-13%), tocilizumab (6.5-27%), remdesivir (3-8%), infliximab (1.2-8%), and plasma (n � 3) [24,26,27,29,[36][37][38]. Intravenous immunoglobulin combined with methylprednisolone compared to intravenous immunoglobulin alone is significantly effective in reducing fever, the need for second-line drug therapy, hemodynamic support, and length of intensive care stay [39].…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, male/female ratio was 1.37:1, and the median age was 7.5 years in another systematic review including 992 MIS-C patients. 14 It is well known that the current pandemic was originated from East Asia. Besides, KD is in the differential diagnosis of MIS-C mostly seen in Asian children.…”
Section: Epidemiologymentioning
confidence: 99%
“…There was a slight male predominance, and cases were mostly school-age children and adolescents, similar to the current literature. 13,14 While the PCR tests were negative in most of them, they were seropositive against SARS-CoV-2. Fever and gastrointestinal symptoms were the most common symptoms.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…We thank the reader for reading our review with interest [ 1 ]. This review was undertaken and reported in accordance with the preferred reporting items for systematic review and meta-analyses (PRISMA) guidelines [ 2 ].…”
mentioning
confidence: 99%
“…This review was undertaken and reported in accordance with the preferred reporting items for systematic review and meta-analyses (PRISMA) guidelines [ 2 ]. The details have been shared in the supplementary material [ 1 ].…”
mentioning
confidence: 99%